A Fourth Circle of English. Issue 1 (3rd June 2019) - Pandey, Anita
Abstract: This paper identifies a Fourth Circle of English, fueled by technology and outsourcing, and exemplified by the Indian speech community known as 'youngistan.' A variety of data are examined, including YouTube and other online advertisements, social media posts and exchanges, texts, as well as secondary data. To ensure a comprehensive and empirical account, the data are analyzed using applicable frameworks of critical discourse analysis, including Braj Kachru's world Englishes model premised on the notions of context‐specific, geographic interpretations through the tripartite constructs acceptability, comprehensibility, and intelligibility. In the case of the interactive exchanges examined, conversational analysis was employed, as well. In addition to the researchers' assessment, the interpretations of undergraduate students in a Business Writing Course taught by the professor at Morgan State University, a historically black college and university (HBCU) are shared. The paper ends by discussing the implications of the types of language contact phenomena observed, before outlining directions for future research.